Utilization of Poultry Slaughterhouses (PSh) Waste as a By-product of Protein Sources to Create the Environmental Friendly Livestock Systems in Makassar, South Sulawesi, Indonesia - Irfan Said, Muhammad; Abustam, Effendi; Pakiding, Wempie; Zain Mide, Muhammad (European Journal of Sustainable Development, 2019)
Livestock waste is one of the important problems in a livestock farming system. Various efforts was needed to reduce waste production. The use of waste is one of solution in reducing waste production to create an environmentally friendly livestock farming system. Utilization of livestock waste from PSh as feed ingredients for alternative protein sources can reduce the cost of feed use. This has an impact on a more efficient livestock business. The feather from the poultry contains high protein compounds. The application of waste from the poultry feather as a source of animal feed to improve the quality of quail meat has not been widely reported. The aim of the study was to examine the effect of giving feather waste extract (FWE) on the quality of thigh meat (Bicep femoris) for quail. A total of 100 heads quails, male, were used as samples. A total of 4 types of FWE administration treatments have been applied. Four types of FWE treatment have been applied in this study, namely: (FA = 0%; FB = 1%; FC = 1.5% and FD = 2%). Each treatment unit was repeated 5 times with 5 heads quail samples/treatment. The results showed that the application of FWE at different levels had a significant effect (p<0.05) on cooking loss (CL) and shear force (SF) of thigh meat (Bicep femoris), whereas in water holding capacity (WHC) it did not show a significant effect (p>0.05). The value of the WHC of thigh meat (Biceps femoris) is in the range of 33.33±1.65%-42.07±5.01%, MSF of 0.40±0.05-0.93±0.18 kg/cm2 and CL of 6.10±2.70-19.90±4.51%. An application of 2% FWE in feed mixtures showed better meat quality of thigh meat (Bicep femoris). An application of FWE as a protein source for animal feed can be improve the environmental sustainability and create a more efficient livestock business. Keywords: Poultry slaughterhouse (PSh), By-product, Protein, Feather waste extract (FWE), Environmental friendly